Dampak Bunga (Riba) Terhadap Perkembangan Perbankan Syari’ah di Indonesia - Nicky Nanda Putri Dalimin; Risti Febri Astuti; Meylani Anggitasari; Alifah Nur Fatin; Lisa Oktavia Ramadhani; Reswara Tsalits; Anang Hidayah; Fariska Sari; Nur Rofiq (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This article tries to raise the theme of the impact of interest (usury) on the development of sharia banking in Indonesia. In the Islamic view, interest paid by conventional banks is included in usury. The practice of usury isu haram because usury is an act that exceeds the nominal amount of the loan. This action is contrary to the teachings of the Islamic religion, Islamic teachings do not allow making additions in the wrong way which can cause injustice. The research method used is a qualitative method by collecting several materials, legal sources and other comparative research materials. This qualitative method uses a secondary approach. A secondary approach can make it easier to obtain discussions from various references and information from various literature studies. The materials and objects used are journals and books. To strengthen understanding, the author emphasizes looking for various relevant journals and various opinions of figures. The research results show that the practice of bank interest (usury) cannot be avoided in the banking industry as a financial institution and an intermediation medium between surplus units (lenders) and deficit units (borrowers). Riba is additional (ziyadah) without compensation that occurs due to delays in previously agreed payments. There are 2 types of usury which can be grouped into 2, namely debt usury and buying and selling usury. The prohibition of usury has also been regulated in several verses and authentic hadiths where a person is commanded to avoid usury because it will harm oneself and others. Overcoming this requires efforts to avoid losses due to the negative impacts it causes. As a result, it creates various economic impacts felt by society, such as gaps in economic growth.